Reduced ADAM8 levels upon non-surgical periodontal therapy in patients with chronic periodontitis - Tanawat Nimcharoen (2018)
© 2018 Objective: To determine effect of non-surgical periodontal treatment on a disintegrin and metalloproteinase 8 (ADAM8) levels in gingival crevicular fluid (GCF) of patients with chronic periodontitis (CP) in comparison with those of patients with gingivitis and to find correlations between ADAM8 levels and clinical parameters. Design: Twenty-two and eleven patients with CP and gingivitis, respectively, were examined for four clinical parameters, probing depth, clinical attachment level, gingival and plaque indices. GCF from the selected gingivitis or periodontitis sites with distinct severities was sampled by Periopaper strips. The non-surgical treatments, including scaling and/or root planing and oral hygiene instruction, were provided for all patients. Clinical measurements and GCF sampling were repeated at three months after the treatments. ADAM8 concentrations were analyzed by ELISA and normalized by GCF volumes or total protein amounts. Results: All patients exhibited significant improvement of almost every clinical parameter after treatment, whereas the median ADAM8 concentrations were significantly decreased at the moderate and severe periodontitis sites of patients with CP (p < 0.05). Moreover, the significantly positive correlations between ADAM8 concentrations and four clinical parameters were found in both moderate and severe groups (p < 0.05). Conclusion: ADAM8 concentrations were decreased by non-surgical periodontal therapy in patients with chronic periodontitis at the moderate and severe sites and were correlated with four clinical parameters, implying that GCF ADAM8 levels reflect inflammatory and bone-resorbing activities in the periodontal pocket.